Allies at the End of Empire—Loyalists, Nationalists and the Cold War, 1945–76. Issue 1 (1st January 2017) - Anderson, David M.; Branch, Daniel
ABSTRACT: The wars of decolonization fought by European colonial powers after 1945 had their origins in the fraught history of imperial domination, but were framed and shaped by the emerging politics of the Cold War. Militia recruited from amongst the local population was a common feature in all the counter-insurgencies mounted against armed nationalist risings in this period. Styled here as 'loyalists', these militia fought against nationalists. Loyalist histories have often been obscured by nationalist narratives, but their experience was varied and illuminates the deeper ambiguities of the decolonization story, some loyalists being subjected to vengeful violence at liberation, others actually claiming the victory for themselves and seizing control of the emergent state, while others still maintained a role as fighting units into the Cold War. This introductory essay discusses the categorization of these 'irregular auxiliary' forces that constituted the armed element of loyalism after 1945, and introduces seven case studies from five European colonialisms—Portugal (Angola), the Netherlands (Indonesia), France (Algeria), Belgium (Congo) and Britain (Cyprus, Kenya and southern Arabia).